Induced resistance by Bacillus subtilis on oil palm seedling infected by Ganoderma boninense - FIFI PUSPITA; HADIWIYONO; SUSILO HAMBEG POROMORTO; DEWI INDRIYANI ROSLIM (Society for Indonesian Biodiversity, 2020)
Abstract. Puspita F, Hadiwiyono, Poromorto S. H, Roslim D. I. 2020. Induced resistance by Bacillus subtilis on Ganoderma boninense infected oil palm seedling. Biodiversitas 21: 28-33. Basal Stem Rot (BSR) caused by Ganoderma boninense Pat is the most important disease in oil palm plantations. The use of biological resistance inducer is a promising alternative disease-control. The research evaluated the potential and mechanism of endophytic Bacillus subtilis as resistance inducer agent of oil palm seedlings to infection of G. boninense. The Experiment was carried out using a completely randomized design consisting of 4 treatments and 3 replications namely of endophytic B. subtilis with four inoculum densities (0, 1011, 1012, and 1013 cfu.mL-1) on oil palm before inoculation of G. boninense. The observation variables were incubation period, disease intensity, growth and concentration of salicylic acid in leaf extract of oil palm seedlings. In addition, the ability of B. subtilis to produce IAA in liquid Pikovskaya medium enriched by tryptophan was assayed. The results showed that B. subtilis was potential as biological resistance inducer agents of oil palm seedlings to infection of G. boninense. The induced resistance was related to increasing growth, salicylic acid in leaf the seedlings and the capability was assayed to produce IAA.